Political and institutional communication and the media in times of pandemic. Analysis of the dialogue on vaccines in five Ibero-American countries - Peña-Fernández, Simón (2022)
The current media context is characterized as a hybrid system in which old and new actors coexist and, at the same time, compete for their hegemony in the media sphere. In this context, Covid-19 has generated an “infodemic” or information overexposure that has made it difficult for citizens to access reliable sources and guidance. Therefore, the main objective of this article is to characterize the political, institutional and media actors who have reported on Twitter about vaccines and immunization processes during the Covid-19 pandemic in five Ibero-American countries: Argentina, Brazil, Chile, Spain and Mexico. To this end, a total of 68,822 tweets from 84 accounts belonging to the country's presidents, the official accounts of governments, health authorities and their spokespersons, and the main media have been analyzed. The results indicate that the most intense activity and the informative weight have been carried by the health authorities and the media, although the personal accounts of the spokespersons and political representatives have achieved a much greater engagement. The interaction of the audiences has been mostly positive, although the most active users and with the highest level of participation have made comments for the most part negative. These results allow us to conclude that in the hybrid system, the media and institutional communication cabinets show a similar capacity to disseminate messages through social networks that generate a favorable reception, although in the case of public representatives, engagement, and also the polarization, they are much greater.